How will the adoption of the Nairobi WTO 10th Ministerial Conference decisions on cotton impact on the East African Community? - Munu, Martin Luther; Shinyekwa, Isaac (Economic Policy Research Centre, 2018)
In December 2015, the World Trade Organization (WTO) held its 10th Ministerial Conference (MC10) in Nairobi, Kenya. The meeting adopted the “Nairobi package” of decisions targeting agriculture, cotton and issues related to least-developed countries. This brief examines the implications of the Nairobi package for the development of cotton sector in the East African Community (EAC). The results indicate that the removal of subsidies would reduce cotton production among the top producing countries, reducing their export earnings while increasing both production and export earnings in the EAC. Therefore, the EAC needs to monitor the implementation the agreement and increase cotton production to take advantage of the opportunity.